Effect of select menhaden fish meal and dried whey in starter diets for pigs - G R Stoner; G L Allee; Jim L Nelssen; M E Johnston (Kansas Agricultural Experiment Station Research Reports, 1987)
A growth trial was conducted to examine the effects of select menhaden fish meal (SMFM) and dried whey (DW) in starter diets for pigs. A total of 240, 3-wk-old, weaned pigs averaging 12.1 lb were utilized. Pigs did not receive creep feed and were introduced to the experimental diets immediately upon weaning. The trial was conducted for 4 wk. A factorial design with 3 levels of SMFM (0, 4, and 8%) and 2 levels of OW (10 and 20%) was employed. Analysis of the data indicated no SMFM x DW interaction by the end of wk 4. Inclusion of SMFM resulted in a linear response (P<.0l), improving average daily gain (ADG) and feed efficiency (F/G) by the end of wk 4. Although SMFM increased average daily feed intake (ADFI) (P<.10) by the end of wk 2, this effect had dissipated by the end of wk 4. Dried whey had an effect (P<.01) on ADG and ADFI, but no effect on F/G by the end of wk 4. These results show that SMFM and DW work well together in starter diets for the early-weaned pig.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Menhaden fish meal; Dried Whey; Starter pigs